COMMUNITY EMPOWERMENT THROUGH THE CULTIVATION OF OYSTER MUSHROOMS IN IMPROVING THE ECONOMY - Husni, Mohamad; Setianti, Selda; Indriyanto, Irfan; Paamudiaspuri, Aski Atsriya; Agustina, Melly; Dhaifulah, Adhiya Fauzan (Nindikayla Institute, 2024)
Sayar Village has a land area of 1,359,5 hectares with the most significant area being occupied by fields or rice fields of 943 hectares so that the surrounding community works as farmers, but there is still much vacant land that is not utilized optimally by the surrounding community. So, the KKM group 09 Bina Bangsa University carried out an Agricultural Workshop with the theme